Perception of Service Quality and Satisfaction Affectingto Buying Decisions with Suppliers of the Automotive Industry in the Easter Industrial Estate - Anancharoenporn, Amnart; Boriraj, Jumpoth (Journal of Modern Learning Development, 2023)
This article is primarily concerned with service quality and satisfaction affecting to buying decisions products with suppliersby studying the variables of service quality consisting of1) Service concrete. Reliability, 2) Customerresponse,3) Providing confidence in customers,4) Knowing and understanding customers, and 5) Service satisfaction variables consist of: 1) Customer The expectation, 2)Perceived quality of the product or service received by the customer, and 3)Value of the product or service received, and the dependent variable is Making.Purchase decisions with suppliers of inputs. According to many scholars have brought in the factors of service quality to study the impact of service satisfaction and impact on purchasing decisions by scholars foundmuch researchwith service quality factor Affects the effect on service satisfaction and service satisfaction have a direct impact on purchase decision of the sample.